Is the hedging efficiency of weather index insurance overrated? A farm-level analysis in regions with moderate natural conditions in Germany. Issue 3 (23rd February 2018) - Doms, Juliane; Hirschauer, Norbert; Marz, Michael; Boettcher, Falk
Abstract : Purpose: The purpose of this paper is to analyze the hedging efficiency (HE) of weather index insurances (WII) based on a whole-farm approach. The aim is to identify how different types of WII affect the economic performance risk of real farms in the light of the heterogeneity of farm operations and natural conditions. Design/methodology/approach: Using historic simulation, the HE of various hedging strategies is computed for 20 farms in regions with moderate natural conditions. A priori defined "standardized" WII and hedge ratios as well as ex post "optimized" strategies are analyzed. The latter is identified through a risk programming approach that determines the strike level and hedge ratio that would have minimized the volatility of each farm's historic total gross margins (TGMs) ex post . Findings: (i) The correlations between the weather indexes and the yields of the farms' main crop (wheat) do not provide useful insights regarding the whole-farm HE because farms' performance risk is considerably affected by volatile factors other than wheat yield; (ii) Standardized WII are ill-suited to hedge performance risk for the majority of studied farms; (iii) A considerable positive whole-farm HE could have been obtained on average if farmers had been able to use the "optimized" risk management strategy. Using farm-specific information thus seems to be essential for identifying meaningful hedging strategies. Originality/value: This study provides added value by analyzing the HE of WII for 20 German crop farms in "moderate" regions. The results show that exemplary tests of WII in extreme conditions provide no decision support for farmers in other regions.